New Predictor of Organ Failure in Acute Pancreatitis: CD4+ T Lymphocytes and CD19+ B Lymphocytes. (5th December 2018) - Shi, Chenyuan; Hou, Chaoqun; Zhu, Xiaole; Peng, Yunpeng; Guo, Feng; Zhang, Kai; Huang, Dongya; Li, Qiang; Miao, Yi
Abstract : Objective . Lymphocytes are one of the main effector cells in the inflammatory response of acute pancreatitis (AP). The purpose of the study was to evaluate whether peripheral blood lymphocyte (PBL) subsets at admission change during AP based on clinical outcomes and to explore whether these changes vary by aetiology of AP. Hence, we performed a prospective study to find a predictor in lymphocyte subsets that might allow easier, earlier, and more accurate prediction of clinical outcomes. Methods . Patients with AP were enrolled from December 2017 to June 2018 at the First Affiliated Hospital of Nanjing Medical University. Age, sex, clinical and biochemical parameters, and aetiology of AP were obtained at admission. PBL counts were assessed within 24 hours after admission. Clinical outcomes were observed as endpoints. The areas under the curve (AUCs) of different predictors were calculated using the receiver operating characteristic (ROC) curve. Results . Overall, 133 patients were included. Patients (n=24) with organ failure (OF) had significantly lower CD4+ T lymphocyte levels than those (n=109) with No OF (NOF) (39.60 (33.94-46.13) vs. 32.41 (26.51-38.00), P=0.004). The OF group exhibited significantly higher CD19+ B lymphocytes than the NOF group (16.07 (10.67-21.06) vs. 23.78 (17.84-29.45), P=0.001). Of the AP cases, 68.8% were caused by gallstones; 10.1% were attributed to alcohol; 16.5% were due to hyperlipidaemia; and 4.6% had other causes. Across all aetiologies, a lower CD4+ T lymphocyte level was significantly related to OF (P<0.05). However, CD19+ B lymphocytes were significant only in gallstone pancreatitis (P<0.05). The ROC curve results showed that the AUC values of CD4+T lymphocytes, CD19+ B lymphocytes, and combined CD4+T lymphocytes and CD19+ B lymphocytes were similar to those of traditional scoring systems, such as APACHEII and Ranson. Conclusions . CD4+ T and CD19+ B lymphocytes during the early phase of AP can predict OF.